1996
DOI: 10.1093/humrep/11.suppl_4.131
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow-up study of 877 children born after intracytoplasmic sperm injection (ICSI), with ejaculated epididymal and testicular spermatozoa and after replacement of cryopreserved embryos obtained after ICSI

Abstract: A prospective follow-up study of 877 children born after ICSI was carried out. The aim of this study was to compile data on karyotypes, congenital malformations, growth parameters and developmental milestones so as to evaluate the safety of this new technique. The follow-up study included agreement to genetic counselling and prenatal diagnosis and was based on a physical examination at the Centre for Medical Genetics (Dutch-speaking Brussels Free University, Brussels, Belgium) at 2 months, 1 year and 2 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(57 citation statements)
references
References 15 publications
0
51
1
5
Order By: Relevance
“…32 They found none among 29 children conceived using TESE, 1 out of 29 (3.4%) MESA and 21 of 797 (2.6%) standard ICSI. Such small numbers for the non-ejaculated sperm groups are almost meaningless in the context of congenital malformations and it has taken many years for numbers to build up at IVF centres and within registries so that comparisons can be made.…”
Section: Overall Defectsmentioning
confidence: 92%
“…32 They found none among 29 children conceived using TESE, 1 out of 29 (3.4%) MESA and 21 of 797 (2.6%) standard ICSI. Such small numbers for the non-ejaculated sperm groups are almost meaningless in the context of congenital malformations and it has taken many years for numbers to build up at IVF centres and within registries so that comparisons can be made.…”
Section: Overall Defectsmentioning
confidence: 92%
“…If this is done then we might be in a position to finally address the question of whether increased sperm aneuploidy leads to a corresponding increase in aneuploid conceptuses. Results thus far have been encouraging (Bonduelle et al, 1996(Bonduelle et al, , 1999(Bonduelle et al, , 2002Aran et al, 2003); however, a small increase for sex chromosome abnormalities has been reported. Only through accurate assessment of sperm disomy before ICSI, followed up by rigorous clinical and cytogenetic follow-up, will the risks of sperm disomy through infertility treatment be established.…”
Section: Technical Issuesmentioning
confidence: 99%
“…Many aspects are still not understood. This raises concern in terms of so far undetected risks, even though follow-up data after ICSI report only a slight (but statistically relevant) increase in sex-chromosomal and de novo structural chromosome abnormalities [7,8]. There is a special fear of genetic consequences or long-term effects.…”
Section: Introductionmentioning
confidence: 99%